PENGGUNAAN SCIENTIFIC EVIDENCE DALAM PENYELIDIKAN DAN PENYIDIKAN SEBAGAI UPAYA PENEGAKAN HUKUM LINGKUNGAN HIDUP DI WILAYAH POLDA SUMUT - Rusdi Marzuki; Alvi Syahrin; Madiasa Ablisar; Mahmud Mulyadi (USU LAW JOURNAL, 2017)
ABSTRACT Research and investigation is one of the Polri's duties for the community, because the Police is formed from the community and work for the community, the Police must be Professional, Modern and Trusted (Promoter). In this case, environmental crime investigations are carried out through stages of: investigation, prosecution, examination, and settlement and submission of case files. The essence of investigation in the field of environment is done by gathering information (Pulbaket) and making Investigative Results Report by expert. Based on Article 96 of Law no. 32 of 2009 on the Control and Management of the Environment, the legal evidence in the environmental crime suit consists of: testimony of witnesses, experts, letters, instructions, statements of the accused, and / or other evidence. Other evidence is what is referred to as scientific evidence. Reports / Letters made by experts may be referred to as scientific evidence. Scientific evidence is necessary because in the proof of environmental crime cases generally have difficulty in the presentation and determination of causality relationships. Environmental proofs are often confined to the presentation of facts and evidence tools that are often scientific (scientific proof) and involve company secrets. Moreover, if a company suspected of carrying out environmental offenses of more than one amount and disposing of waste containing the same elements, especially those that are chemical and related to Article 183 of the Criminal Procedure Code, which affirms the verdict shall be proved by two valid evidences. Keywords : The use of scientific evidence; researches and investigations; and enforcement of environmental law in the territory of North Sumatra Police.